Pengaruh CAR, LDR dan NPL Terhadap Profitabilitas Pada Bank Yang Terdaftar Di Bursa Efek Indonesia (BEI) (Studi KasuS PT.Bank Bukopin Tbk Tahun 2005-2018) - Sri Devi Apriani; Lousiani Mansoni (Jurnal Ekonomi Manajemen Perbankan, 2019)
The purpose of this study is to analyze the effect of the CAR, LDR, and NPL on the Profitability of Banks Listed on the Indonesia Stock Exchange. The sample in this study is PT Bank Bukopin for 13 years, from 2005 to 2018. Data contained in this study are secondary data, namely the empirical method with a descriptive and verification analysis approach. The data analysis technique used is multiple linear regression analysis with the help of the program Eviews 9 and SPSS 16 so as to get a comprehensive picture of the relationship between variables one with other variables. Hypothesis testing uses t-statistics to test the regression coefficients partially and F-statistics to test the significance of the effects together with a significance level of 5%. In addition, classic assumptions were also carried out including normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. The results of this study are that the CAR, LDR, and NPL variables do not significantly affect ROA partially at a significance level of less than 5%. And the results of simultaneous regression analysis show that CAR, LDR, and NPL together influence ROA. The predictive ability of the three variables on ROA is 56% while the remaining 44% the influence of other factors not included inthe study.